Global prevalence of insulin resistance in the adult population: a systematic review and meta-analysis - Ballena-Caicedo, Jhosmer; Zuzunaga-Montoya, Fiorella E.; Loayza-Castro, Joan A.; Bustamante-Rodríguez, Juan Carlos; Vásquez Romero, Luisa Erika Milagros; Tapia-Limonchi, Rafael; De Carrillo, Carmen Inés Gutierrez; Vera-Ponce, Víctor Juan (Frontiers in Endocrinology, 2025)
ObjectiveTo determine the global prevalence of IR, evaluating differences according to study designs and population characteristics.MethodologyA systematic review with meta-analysis was conducted. The search encompassed MEDLINE (PubMed), Scopus, Web of Science, and EMBASE, including observational studies that employed the HOMA-IR index to estimate IR and published adult prevalence data. Articles without clear IR definitions or with highly specific populations were excluded. The meta-analysis applied a random-effects model with proportion transformation (Freeman-Tukey), assessing heterogeneity with I² and Cochran’s Q test. Additionally, a meta-regression by publication year was conducted.ResultsEighty-seven studies were included, with 235,148 participants. The pooled prevalence of IR was estimated at 26.53% (95% CI: 24.10–29.03; I²=99%), with no statistically significant differences when comparing probabilistic versus non-probabilistic sampling or when stratifying by sex. The meta-regression revealed no clear variations according to publication year or other explored factors.ConclusionsThis systematic review demonstrates that IR reaches a global prevalence of 26.53%, with estimated differences between 26% and 30% across different populations and geographical regions. Despite the diversity in cut-off points employed for HOMA-IR, no statistically significant differences were observed when comparing sampling designs or stratifying by sex. Furthermore, no clear trend related to publication year was evidenced.